2014
DOI: 10.1002/mds.25944
|View full text |Cite
|
Sign up to set email alerts
|

Action inhibition in Tourette syndrome

Abstract: Tourette syndrome is a neuropsychiatric disorder characterized by tics. Tic generation is often linked to dysfunction of inhibitory brain networks. Some previous behavioral studies found deficiencies in inhibitory motor control in Tourette syndrome, but others suggested normal or even better-than-normal performance. Furthermore, neural correlates of action inhibition in these patients are poorly understood. We performed event-related functional magnetic resonance imaging during a stop-signal reaction-time task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 58 publications
2
69
1
3
Order By: Relevance
“…Less sensorimotor beta desynchronization shown by TS patients contralaterally to the responding hand is in keeping with the assumption of increased tonic inhibition in these patients, probably to suppress tics. 5 Beta upregulation in the motor cortex was associated with improved behavioral outcome in a holding contraction task in healthy subjects. 20 The beta FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Less sensorimotor beta desynchronization shown by TS patients contralaterally to the responding hand is in keeping with the assumption of increased tonic inhibition in these patients, probably to suppress tics. 5 Beta upregulation in the motor cortex was associated with improved behavioral outcome in a holding contraction task in healthy subjects. 20 The beta FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed a reduced activation in the dorsal premotor cortex for the StopSuccess trial. 21 The conflicting results might be caused by a difference in study design: in Ganos et al's study, 21 the procedure was adapted to ensure a fifty-fifty successful performance in the no-go trials in both patients and controls, whereas in Thomalla et al's study, 22 there were behavioral differences between patients and controls. The patients with TS were slower and and made more mistakes in no-go trials than the healthy controls.…”
Section: Functional Correlates Of Inhibitory Motor Controlmentioning
confidence: 99%
“…21,22 Go/ no-go test is a test of behavioral control in which an appropriate reaction must be performed and an inappropriate reaction must be inhibited. Results are contradictory.…”
Section: Functional Correlates Of Inhibitory Motor Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…These cortical regions, along with their connections to the basal ganglia, comprise the brain's inhibitory control network, a network that is variably impacted in adults with persistent TS. 10,35 Moreover, Ganos et al 36 identified functional changes in this network between TS and controls performing a stop-signal task. It should be recognized that several measures of inhibitory control used in the TS literature are not entirely interchangeable, but capture distinct forms of inhibitory control associated with dissociable neural mechanisms.…”
Section: Discussionmentioning
confidence: 99%